2015
DOI: 10.17718/tojde.21716
|View full text |Cite
|
Sign up to set email alerts
|

Modular Rapid E-Learning Framework (MORELFT) in Desktop Virtualization Environment: An Effective Hybrid Implementation in Nurse Education

Abstract: Generally it is not easy for an instructor to prepare and deliver electronic courses via elearning. Therefore it is necessary to work and develop an easy system. In this context module technology was used to for provide modularity in conducting educational development of elearning course. Then, rapid e-learning was used for more quick and easy course development. In order to implement modular rapid e-learning, a desktop virtual environment was set up. Modular rapid e-learning was used by teachers and students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(2 reference statements)
0
1
0
1
Order By: Relevance
“…Studies have been conducted on the nature of modular learning globally (Parlakkilic, 2015;Dejene, 2019) and in the Philippines (Zulueta & Guimbatan, 2002;Unay et al, 2016). Other studies also have identified the effects of modular learning on the learning process (Cornford, 1997;Matanluk et al, 2013;Cabrera, 2014;Lim, 2016) and student performance (Chua et al, 2007;Bedaure, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted on the nature of modular learning globally (Parlakkilic, 2015;Dejene, 2019) and in the Philippines (Zulueta & Guimbatan, 2002;Unay et al, 2016). Other studies also have identified the effects of modular learning on the learning process (Cornford, 1997;Matanluk et al, 2013;Cabrera, 2014;Lim, 2016) and student performance (Chua et al, 2007;Bedaure, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these exploratory analyses we can conclude that the managerial changes [36] in the course basically increased the visit rate on the selected activities, which helped the students to receive better evaluation results from the subject.…”
Section: Discussionmentioning
confidence: 94%
“…I uddannelsesregi har spørgsmålet om online uddannelsers laeringsmaessige kvalitet, sammenlignet med campusbaserede uddannelser, vaeret et omdrejningspunkt (Lahti et al, 2014;Li, 2013;McCutcheon et al, 2015;Parlakkilic, 2015;Voutilainen, 2017). Tilsvarende har e-paedagogiske retninger vaeret debatteret og eksempelvis knyttet til spørgsmålet om kollaborativ laering.…”
Section: Baggrundunclassified